2000
DOI: 10.1074/jbc.m002118200
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Mutagenesis of Conserved Arginine and Tryptophan Residues in Rat Liver Carnitine Palmitoyltransferase I Important for Catalytic Activity

Abstract: Carnitine palmitoyltransferase I catalyzes the conversion of long-chain acyl-CoA to acylcarnitines in the presence of L-carnitine. To determine the role of the conserved arginine and tryptophan residues on catalytic activity in the liver isoform of carnitine palmitoyltransferase I (L-CPTI), we separately mutated five conserved arginines and two tryptophans to alanine. Substitution of arginine residues 388, 451, and 606 with alanine resulted in loss of 88, 82, and 93% of L-CPTI activity, respectively. Mutants R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…For M-CPTI, our mutagenesis studies demonstrate that in addition to Glu-3 and His-5, Val-19, Leu-23, and Ser-24 are necessary for malonyl-CoA inhibition and high affinity binding, in agreement with the differences in malonyl-CoA sensitivity observed between M-CPTI and L-CPTI (17). In addition, our site-directed mutagenesis studies of conserved residues in the C-terminal domain of L-CPTI demonstrated that conserved arginine and tryptophan residues are important for catalysis (18). In this report, our mutagenesis studies demonstrate for the first time that the conserved residues Arg-601, Glu-603, and Arg-606 in L-CPTI are important for catalytic activity and malonyl-CoA sensitivity.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…For M-CPTI, our mutagenesis studies demonstrate that in addition to Glu-3 and His-5, Val-19, Leu-23, and Ser-24 are necessary for malonyl-CoA inhibition and high affinity binding, in agreement with the differences in malonyl-CoA sensitivity observed between M-CPTI and L-CPTI (17). In addition, our site-directed mutagenesis studies of conserved residues in the C-terminal domain of L-CPTI demonstrated that conserved arginine and tryptophan residues are important for catalysis (18). In this report, our mutagenesis studies demonstrate for the first time that the conserved residues Arg-601, Glu-603, and Arg-606 in L-CPTI are important for catalytic activity and malonyl-CoA sensitivity.…”
mentioning
confidence: 67%
“…Substitution of Glu-603 with glutamine resulted in a 92% loss in L-CPTI activity and a 14-fold decrease in malonyl-CoA sensitivity (Table II). We previously reported that mutation of the highly conserved arginine residues Arg-601 and Arg-606 to alanine resulted in Ͼ98 and 93% loss in L-CPTI activity, respectively (18). The loss in activity observed with the R601A and R606A mutants was also accompanied by decreased sensitivity to malonyl-CoA inhibition (18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations